Development of a new TaqMan-based real-time RT-PCR assay for the specific detection of bovine kobuvirus - Liu, Yuelin; Liu, Libing; Wang, Jinfeng; Wang, Ting; Gao, Yaxin; Sun, Xiaoxia; Yuan, Wanzhe; Li, Ruiwen; Wang, Jianchang (Frontiers in Veterinary Science, 2022)
Bovine kobuvirus (BKV) is a novel kobuvirus considered to be closely related to calf diarrhea and has become a worldwide epidemic. Currently, the BKV lacks an efficient and convenient detection method to assist the research on BKV prevalence. In this study, a new and specific TaqMan-based real-time RT-PCR for the detection of BKV was developed using the conserved region of the 3D gene. The assay was highly specific for BKV, without cross amplification with other non-targeted pathogens. The limit of detection of this assay was 102 copies. Standard curves showed a strong linear correlation from 102 to 106 copies of BKV standard RNA per reaction, and the parameters revealed as a slope of -3.54, efficiency of 91.64% and regression coefficients (R2) of 0.998. The assay was also very reproducible, with the intra-assay and inter-assay coefficient of variation less than 1.0%. The newly developed real-time RT-PCR was validated using 243 fecal samples collected from diarrheic or non-diarrheic cattle from nine regions in Hebei province and revealed the positive detection of BKV at the ratio of 19.34% (47/243). Sequencing of partial 3D genes from 13 positive samples and the following phylogenetic analysis demonstrated the reliability of the assay. In conclusion, the newly developed TaqMan-based real-time RT-PCR could be used for the screening and epidemic monitoring of BKV.